2011
DOI: 10.1371/journal.pntd.0000932
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Sclerosing Panencephalitis in Papua New Guinean Children: The Cost of Continuing Inadequate Measles Vaccine Coverage

Abstract: IntroductionSubacute sclerosing panencephalitis (SSPE) is a late, rare and usually fatal complication of measles infection. Although a very high incidence of SSPE in Papua New Guinea (PNG) was first recognized 20 years ago, estimated measles vaccine coverage has remained at ≤70% since and a large measles epidemic occurred in 2002. We report a series of 22 SSPE cases presenting between November 2007 and July 2009 in Madang Province, PNG, including localized clusters with the highest ever reported annual inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…2 The global incidence of SSPE is not known, but a study from the USA extrapolated data and concluded a risk of 6.5 to 11 cases of SSPE for each 100 000 cases of measles. 6 Similarly high incidence rates are reported in India, which are assumed to be related to crowded living environments and poor vaccination coverage. 4 A study from California found that the incidence of SSPE was 1 in 1367 for children younger than 5 years of age and 1 in 607 for those younger than 1 year of age when they had contracted measles.…”
Section: Epidemiologymentioning
confidence: 91%
“…2 The global incidence of SSPE is not known, but a study from the USA extrapolated data and concluded a risk of 6.5 to 11 cases of SSPE for each 100 000 cases of measles. 6 Similarly high incidence rates are reported in India, which are assumed to be related to crowded living environments and poor vaccination coverage. 4 A study from California found that the incidence of SSPE was 1 in 1367 for children younger than 5 years of age and 1 in 607 for those younger than 1 year of age when they had contracted measles.…”
Section: Epidemiologymentioning
confidence: 91%
“…Children with severe anemia (hemoglobin concentration <50 g/L) were identified as part of an observational study of all children aged 0.5–10 years admitted to the pediatric ward of Modilon Hospital, the tertiary referral hospital for Madang Province, between October 2006 and November 2009 [20], [21]. Healthy non-anemic children (hemoglobin concentration >100 g/L), matched where possible by age and sex, were recruited as controls from community-based immunization clinics.…”
Section: Methodsmentioning
confidence: 99%
“…After excluding children who did not have an admission lumbar puncture and those with a primary or co-incident non-malarial illness caused by locally prevalent bacterial, viral, or fungal pathogens as confirmed by blood/CSF culture, and/or specific antigen, serologic, and/or polymerase chain reaction testing, as well as Indian ink staining, [5][6][7] children with blood slide-positive malaria confirmed by polymerase chain reaction were assigned to one of three sub-groups: 1) cerebral malaria (Blantyre coma score 2 8 and 1,000 P. falciparum or 250 P. vivax asexual parasites/μL); 2) malaria with cerebral involvement (parasitemia as in sub-group 1 but a Blantyre coma score of 3 or 4 and/or complex febrile seizures); and 3) malaria admissions (any parasite density and a normal level of consciousness with or without other signs of severity, 8 including single convulsions). Complex seizures were defined as multiple ( 2 episodes), prolonged ( 15 minutes), or focal (unilateral).…”
mentioning
confidence: 99%